Analisis Career path, Personal Branding & Religious Marketing terhadap Keputusan Melanjutkan Pendidikan - Subekti, Winda; S, Ramli; Aqil, Muhammad (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
Marketing competence in educational institutions, especially universities, must use marketing strategies that are tailored to the needs and desires of the current community so that the interest of prospective students can be obtained. Therefore, it is necessary to carry out new studies that can be used to attract student interest. The aim of this research is to analyze the influence of career path, personal branding & religious marketing on the decision to continue education at the undergraduate program at Muhammadiyah University, Mamuju. This research is quantitative research using descriptive and explanatory research approaches. The sample in the research was taken using the Slovin formula with a sample of 226 respondents. Sampling took the form of simple random sampling. The survey was distributed online using Google Form to new students class 2023/2024. Data analysis took the form of validity, reliability, partial and simultaneous tests as well as multiple linear regression analysis methods using SPSS version 24.0 software. The results of the research show that: (1) career path has a direct and significant influence on the decision to continue education, both partially (individually) and simultaneously (together) for undergraduate students at Muhammadiyah University, Mamuju; (2) personal branding has a significant influence, both directly and indirectly, on undergraduate programs at Muhammadiyah University, Mamuju. (3) Religious marketing has a direct influence on undergraduate programs at Muhammadiyah University, Mamuju.